Theatre History and Historiography - Cochrane, Claire. author. aut Link
XIII, 205 p.
Keywords: This collection of essays explores how historians of theatre apply ethical thinking to the attempt to truthfully represent their subject - whether that be the life of a well-known performer, or the little known history of colonial theatre in India - by exploring the process by which such histories are written, and the challenges they raise.